2011
DOI: 10.1113/jphysiol.2011.215814
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating motor cortex from the motor

Abstract: During closed-loop control of a brain-computer interface, neurons in the primary motor cortex can be intensely active even though the subject may be making no detectable movement or muscle contraction. How can neural activity in the primary motor cortex become dissociated from the movements and muscles of the native limb that it normally controls? Here we examine circumstances in which motor cortex activity is known to dissociate from movement -including mental imagery, visuo-motor dissociation and instructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 73 publications
0
54
0
Order By: Relevance
“…According to a hierarchical view of motor control (Kawato et al, 1987;Loeb et al, 1999;Konen and Kastner, 2008) dexterous manipulation capabilities, such as the compression of an unstable spring prone to buckling, are likely not exclusively controlled Q7 by the neo-and somatosensory cortices (Lawrence et al, 2014;Lemon, 1993;Schieber, 2011) but involve also subcortical and spinal structures (Lawrence et al, 2014). Even if we presume a limited role of the spinal cord in movement generation in humans, the spinal cord can certainly shape the motor commands coming from supraspinal structures by gating, inhibiting, or disinhibiting the behavior of spinal circuitry (Pierrot-Deseilligny and Burke, 2005).…”
Section: 4mentioning
confidence: 99%
“…According to a hierarchical view of motor control (Kawato et al, 1987;Loeb et al, 1999;Konen and Kastner, 2008) dexterous manipulation capabilities, such as the compression of an unstable spring prone to buckling, are likely not exclusively controlled Q7 by the neo-and somatosensory cortices (Lawrence et al, 2014;Lemon, 1993;Schieber, 2011) but involve also subcortical and spinal structures (Lawrence et al, 2014). Even if we presume a limited role of the spinal cord in movement generation in humans, the spinal cord can certainly shape the motor commands coming from supraspinal structures by gating, inhibiting, or disinhibiting the behavior of spinal circuitry (Pierrot-Deseilligny and Burke, 2005).…”
Section: 4mentioning
confidence: 99%
“…However, a large fraction of the mirror PTNS in M1 showed suppression of discharge during action observation (Kraskov et al , 2014); some cortico-motoneuronal PTNs also showed this suppression. One suggested role for these suppression mirror neurons relates to involvement in withholding unwanted movement during action observation, and that such a braking mechanism would avoid unintended overflow of activity (Schieber, 2011).…”
Section: Als Hand Function and Mirror Neuronsmentioning
confidence: 99%
“…Davidson et al (2007) and Schieber (2011) called a similar disparity between activity of M1 neurons and EMGs, "dissociating motor cortex from the motor." In their experiments, monkeys were rewarded for synchronous activation of specific motor neurons and arbitrary muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The now classic STA approach, which effectively represents cross-correlation between single neurons and EMGs, was introduced to assess functional connectivity of spinal motoneurons Jackson et al 2006;Mantel and Lemon 1987;McKiernan et al 2000;Miller et al 1993;Morrow and Miller 2003;Schieber and Rivlis 2007). This and similar methods have been used to analyze the inputs to the spinal cord from the cortex (Carmena et al 2003;Davidson et al 2007;Fuglevand 2011;McKiernan et al 2000;Morrow et al 2007;Schaefer et al 2009;Schieber 2011), red nucleus (Miller et al 1993) and reticular formation (Stuphorn et al 1999). The analytic approach employed in the present study, JCC, is very similar to the JPSTH method introduced in the late 1960s for the analysis of time-dependent correlations between neurons (Aertsen et al 1989;Cardoso de Oliveira et al 2001;Gerstein and Perkel 1969;Vaadia et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation